Valorização energética de um complexo enzimático em dietas de poedeiras em segundo ciclo de produção sobre o desempenho produtivo e qualidade dos ovos - Santos, Verônica Lisboa (2012)
In poultry production systems, molting procedure and the use of substitutes for corn and soybean meal represents good ways to reduce feed costs in poultry production. That s true because farmers skip rearing phase of layers life using molting procedure and the use of grains with similar nutritional requirements as corn and soybean meal are less expensive than those usual used in poultry diets. In this case, whole rice brain (WRB) it s consider a good choice due to its high production and lower market price, justifying the use in animal diets. However, higher levels of WRB in poultry diets show negatives effects due to antinutritional factors as phytic acid and non-starch polysaccharides. Adding enzymes in WRB diets it s a way to increase digestibility and reduce the negative aspects of this factors. During 112 days, divided in four production cycles of 28 days each, performance and egg quality of layers after molting and fed with WRB diets with different energy valorization levels and supplemented with enzymes were evaluated. A total of 480 Hisex Brown layers with 95 weeks old were randomly distributed in groups of five birds per cage in a dark house poultry facility. Treatments consists in 8 different diets, with 12 replicates per treatment, as following: T1: control corn and soybean meal (C+SBM); T2: C+SBM with enzyme supplementation (ES) on top; T3: C+SBM, without ES (100 kcal ME/Kg); T4: C+SBM, with ES (100 kcal ME/Kg); T5: C+SBM, 20% WRB, without ES; T6: C+SBM, 20% WRB, with ES on top; T7: C+SBM, 20% WRB, without ES (100 kcal ME/Kg); T8: C+SBM, 20% WRB, with ES (100 kcal ME/Kg). Performance parameters evaluated were body weight (BW), feed intake (FI), egg production (%EP), feed conversion per dozen (FC/dz) and per mass (FC/m). The parameters used to determine egg quality were egg weight (EW), egg mass (EM), specific gravity (SG), shell thickness (ST), shell weight (SW), Haugh unit (HU), yolk weight (YW), albumen weight (AW) and yolk color (YC). Results showed higher FI, BW, EW and AW in layers fed with WRB diets, which also showed a decrease in YC. Enzyme supplementation and energy valorization (100 kcal ME/Kg) in C+SBM diets improved FC/dz.